Evaluating Tourism SME Development Programs Through Customer Satisfaction as Behavioral Capital: A Time-Lagged Study in Malang City - Wulandari, Wahju; Sasongko, Muhammad Ilman Nur; Kurniawati, Adelia; Gunawan, Ari (Badan Perencanaan Pembangunan Kota Malang, 2026)
Tourism performance is commonly assessed using indicators such as tourist arrivals and tourist spending, which capture short-term economic effects but overlook the behavioral mechanisms that sustain local tourism economies. This study aims to evaluate the effectiveness of regional tourism SME development programs by positioning customer satisfaction as behavioral capital that links policy interventions with market sustainability and regional economic outcomes. A time-lagged sequential explanatory mixed-methods design is employed. Phase 1 evaluates branding-oriented interventions (digital marketing, service quality, and promotion) by examining their effects on customer satisfaction and brand image. Phase 2, conducted after temporal gap, evaluates market sustainability by assessing customer satisfaction and its effects on customer loyalty, repeat purchase behavior, and demand for local souvenir products. Quantitative data were collected longitudinally from 70 customers of Sokressh, a tourism-based SME in Malang City. The qualitative phase uses open-ended questionnaires to explain how customer satisfaction translates into word-of-mouth promotion and local economic circulation. The findings indicate that customer satisfaction significantly mediates both branding and market sustainability outcomes and functions as behavioral capital that drives repeat demand. Qualitative evidence shows that increases in customer satisfaction are associated with higher repeat purchases and stronger tourist recommendations, contributing to stable demand for local products. The study proposes Tourism-Based SME Marketing Sustainability Model and demonstrates that customer satisfaction can serve as a behavioral-based indicator of program effectiveness linking SME support policies with regional economic development. Findings show satisfaction as behavioral capital strengthens local demand, stabilizes SME income, and enhances resilience in tourism-based cities like Malang.